Flood Mapping Using Satellite Images - Φωκέας, Κωνσταντίνος (Πανεπιστήμιο Πελοποννήσου, 2023)
The aim of this thesis is to study the subject of flood mapping utilizing images captured from satellites and machine learning algorithms. Since the rise of ESA’s Copernicus program and the consecutive Sentinel satellites a vast number of freely available images are captured every day expanding the potential applications. With the launch of Sentinel 1 and Sentinel 2 sensing the planet Earth in an unprecedented frequency and spatial resolution, scientists and engineers can now develop tools in order to understand the processes of the Earth and make more informed decisions. Floods are one of the most devastating natural disaster affecting many people each year, causing a lot of deaths, infrastructure damages and loss of properties. In order to mitigate the effects of floods on people. critical decision making is needed, which can be assisted by satellite images and machine learning methods. This study examines the performance of three different machine learning methods in identifying pixels in satellite images containing flooded areas. More specifically, the three tested methods are based on deep learning architecture, transfer learning and traditional swallow learning pixel based semantic segmentation, consequently. In particular, the deep learning method based on the UNET architecture, transfer learning using as backbone the VGG16 network and a traditional method based on decision trees. Experiments involve training models either through strict or through weak supervision as well as multimodal feature spaces, combining sentinel 1 and sentinel 2. Finally, the machine learning techniques are compared in terms of performance with a technique based on the segmentation of the histogram of the image, called as baseline model.
Χαρτογράφηση πλημμυρών με χρήση δορυφορικών εικόνων
Μ.Δ.Ε. 92
Keywords: δορυφορική τηλεπισκόπηση; χαρτογράφηση πλημμυρών; αντιμετώπιση καταστροφών; δορυφορικές εικόνες; εποπτευόμενη σημασιολογική κατάτμηση